Analisis Tingkat Keramahan Lingkungan Alat Tangkap Penggaruk Berkapal (Boat Dredges) di Kecamatan Panggungrejo Kota Pasuruan - Akhmad Subhan; M Tajuddin Noor; Exist Saraswati (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
Panggungrejo District in Pasuruan City is a central hub for fishing activities with significant potential for capture fisheries production. One of the fishing gears used by fishermen in this area is the boat dredge, which is classified as an active fishing gear. This study aims to assess the environmental friendliness of the boat dredge used by fishermen in Panggungrejo based on the principles of the Code of Conduct for Responsible Fisheries (CCRF). The research employs a descriptive method, using data collection techniques such as interviews with structured questionnaires, direct observations, document analysis, and literature review. The study involved 32 respondents consisting of fishermen using the boat dredge. Data analysis was performed by assigning scores based on the principles outlined in the CCRF that are related to sustainability and environmental impact of the fishing gear. The results showed that the boat dredge in Panggungrejo scored a total of 855, with an environmental friendliness score of 26.71. Based on this score, the boat dredge falls into category III, considered “environmentally friendly.” However, several indicators related to resource efficiency and the impact on aquatic ecosystems still need improvement to further enhance the environmental friendliness of this fishing gear. This study provides recommendations for the development and improvement of more environmentally friendly fishing techniques and increasing fishermen’s awareness of sustainability in fisheries practices.